Highly transparent and color-neutral Eu3+-doped glass luminescent solar concentrators for scalable BIPV integration - Ilter, Emre; Ekim, Utku; Celik, Harun Samet; Celikbilek Ersundu, Miray; Ersundu, Ali Ercin (ROYAL SOC CHEMISTRY, 2026)
As urban design increasingly prioritizes energy efficiency and sustainability, building-integrated photovoltaics (BIPVs) have emerged as a compelling approach for on-site solar energy harvesting. Among these, luminescent solar concentrators (LSCs) offer transparent and architecturally compatible solutions by guiding spectrally shifted light to edge-mounted photovoltaic cells. In this study, we report the first demonstration of rare-earth doped (Eu3+) fully inorganic glass based LSCs, combining high optical performance, long-term environmental stability, and process scalability. By tuning the Eu3+ concentration, waveguiding losses are minimized, and the emission efficiency and photon transport are maximized. Devices fabricated with the optimal glass composition (2.5 mm thick; 2 to 6 x 6 cm2) exhibit outstanding average visible transmittance (AVT approximate to 90%) and near-neutral color rendering (CRI approximate to 98), enabling seamless integration into modern architectural environments. The glass matrix maintains its optical and structural integrity under thermal, chemical, and mechanical stress, confirming its long-term durability for real-world applications. External photon efficiency remains stable at similar to 6.4% across all device sizes, while the highest power conversion efficiency (PCE) of 0.852% in the 4-edge configuration is achieved for the most compact device. These findings position Eu3+-doped glass as a robust, scalable, and multifunctional platform for the next generation of BIPV-integrated LSCs, offering a rare-earth-based solution for durable, visually neutral solar harvesting surfaces.
Keywords: COMPLEX; Materials Science; Physics